2020
DOI: 10.1021/acssuschemeng.0c05152
|View full text |Cite
|
Sign up to set email alerts
|

Fe0/Fe2+-Dependent Nitrate Reduction in Anammox Consortia Questions the Enzymatic Mechanism of Nitrate Reduction by Anammox Bacteria

Abstract: The anammox bacteria (AnAOB) have been suggested to perform dissimilatory Fe0/Fe2+-dependent nitrate reduction to ammonium (DNRA), with nitrite as intermediate. However, evidence at genetic and transcriptional levels for how AnAOB reduces nitrate is still lacking, making their roles in this process obscure and questionable. The short-term batch assays and long-term operation of bioreactor combined with 16S rDNA sequencing and transcription analysis were used for the first time to investigate the nitrate reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Ammonia (NH 3 ) is currently one of the most produced chemicals and renewable electricity carriers because of its high energy density (3 kW h kg –1 ) and hydrogen content (17.7 wt %). The industrial production of NH 3 commonly requires harsh conditions and releases a large amount of CO 2 , which has prompted the search for environmentally green technologies. Photoelectrochemical (PEC) technology integrates the comprehensive advantages of photochemistry and electrochemistry to reduce the harmful pollutant nitrate (NO 3 – ) in water to high value-added NH 3 . , Furthermore, the previous report demonstrated that the bacteria can successfully convert NO 3 – to NH 3 by the gene-encoded reductase under mild conditions, where the active sites of reductase were considered to be crucial for photoelectrochemical nitrate reduction reaction (PEC NIRR) . Therefore, the rational construction of active sites becomes a feasible approach to improve the kinetics of PEC NIRR. , …”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 ) is currently one of the most produced chemicals and renewable electricity carriers because of its high energy density (3 kW h kg –1 ) and hydrogen content (17.7 wt %). The industrial production of NH 3 commonly requires harsh conditions and releases a large amount of CO 2 , which has prompted the search for environmentally green technologies. Photoelectrochemical (PEC) technology integrates the comprehensive advantages of photochemistry and electrochemistry to reduce the harmful pollutant nitrate (NO 3 – ) in water to high value-added NH 3 . , Furthermore, the previous report demonstrated that the bacteria can successfully convert NO 3 – to NH 3 by the gene-encoded reductase under mild conditions, where the active sites of reductase were considered to be crucial for photoelectrochemical nitrate reduction reaction (PEC NIRR) . Therefore, the rational construction of active sites becomes a feasible approach to improve the kinetics of PEC NIRR. , …”
Section: Introductionmentioning
confidence: 99%
“…While anammox bacteria grow well with nitrate as the sole nitrogen source, their ability to perform a complete DNRA process was questioned in the present study. Anammox bacteria were shown to express the narG gene for the reduction of nitrate to nitrite in Fe 0 /Fe 2+ -dependent partial DNRA, whereas ammonium was produced from nitrite by abiotic reduction, facilitated by Fe 0 and Fe 2+ (Bi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 ) is an important inorganic chemical product, which is widely used as a raw material in chemical fertilizers and industrial production. [1][2][3][4][5] However, industrial NH 3 production consumes a lot of fuel, while excess fertilizer in the ground leads to increased concentrations of nitrate (NO 3 − ) in groundwater, damaging the ecosystem. [6][7][8] Thus, the reduction of NO 3 − to NH 3 via environment-friendly technology is an ideal pathway to realize the recycling of nitrogen in fertilizer.…”
mentioning
confidence: 99%